1942
DOI: 10.1017/s0022172400035683
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusin the milk of nursing mothers and the alimentary canal of their infants: A report to the Medical Research Council

Abstract: Investigations at two hospitals, P and S, showedStaphylococcus aureusto be commonly present in the milk of healthy nursing mothers and the throat and intestine of their babies. In hospital P, the proportion affected in a group of eighty-two mothers and their babies was over 90%. The condition may not be uncommon in maternity hospitals, but no information of its occurrence is available from private obstetrical practice. The cocci concerned seemed to be of low virulence, for babies swallowing relatively massive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1949
1949
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…This agreed with the findings of others (Duncan & Walker, 1942;Hobbs, 1944;Allison & Hobbs, 1947), who consider that the mother is not an important source of infection. Occasionally, spread from mother to infant undoubtedly does occur, and an example involving a different phage type of Staph.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This agreed with the findings of others (Duncan & Walker, 1942;Hobbs, 1944;Allison & Hobbs, 1947), who consider that the mother is not an important source of infection. Occasionally, spread from mother to infant undoubtedly does occur, and an example involving a different phage type of Staph.…”
Section: Discussionsupporting
confidence: 92%
“…It was the type most commonly isolated from nasal swabs, and was usually present in profuse pure culture. No attempt was made to assess the distribution of the organism in other parts of the body, but it is probable that it was very widespread (Duncan & Walker, 1942;Knott & Blaikley, 1944). In similar circumstances, Allison & Hobbs (1947) have shown that the epidemic type could be isolated from the infants' clothes and bedding.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial colonization of the infant and breast is a normal process that takes place soon after birth. Both the mother’s milk ducts and the infant’s nasopharynx are colonized by a variety of organisms, some of them potentially pathogenic, such as Staphylococcus aureus [ 16 ].…”
Section: The Notion Of Mammary Microbiota Challenges the Concept Of Mmentioning
confidence: 99%
“…Both the mother's milk ducts and the infant's nasopharynx are colonised by a variety of organisms, some of them potentially pathogenic, such as Staph. aureus (38). However, their presence does not by itself cause mastitis (38; 102; 183).…”
Section: Bacterial Colonisation Of the Infant And Breastmentioning
confidence: 99%